Antimicrobial and toxicological analysis of the dry crude extract of catolé coconut epicarp (Syagrus cearensis Noblick) (Research, Society and Development, 2022)
To analyze the toxicological profile of the dry crude extract of the bark of the Coco catolé fruit (Syagrus cearensis Noblick.) against tests with microcrustaceans of Artemia salina Leach and its antimicrobial potential against strains of Staphylococcus aureus, Escherichia coli and Candida albicans fungus. The data from the toxicological tests carried out against Artemia salina L. proved to be moderately toxic, since its LC50 was 347.524 µg/mL, with deaths observed in concentrations from 250 µg/mL. At lower concentrations, such as 100 µg/mL, the microcrustaceans showed slow swimming compared to the standard sample. It was also observed the inhibition of the growth of Staphylococcus aureus and Escherichia coli, from the concentration of 6,25% of the extract, however there was no inhibition of fungi of the genus Candida. Given the assumption, it is concluded that the bark of the S. cearensis species has a relevant therapeutic potential for phytotherapy, and may contribute to new herbal medicines, however, more studies that apply different methodologies should be carried out to control the use of the extract as an antimicrobial agent in drug therapy due to the toxicity reported in the present study.